Life cycle employment and fertility across institutional environments - Daniela Del Boca; Robert M. Sauer (Institute for the Study of Labor (IZA), 2006)
In this paper, we formulate a dynamic utility maximization model of female labor force participation and fertility choices and estimate approximate decision rules using data on married women in Italy, Spain and France. The pattern of estimated state dependence effects across countries is consistent with aggregate patterns in part-time employment and child care availability, suggesting that labor market rigidities and lack of child care options are important sources of state dependence. Simulations of the model reveal that Italian and Spanish women would substantially increase their participation rates were they to face the French institutional environment.
Keywords: 330